(untitled) (Third Sector Social Economic Review, 2026)
Universities function as important economic and social actors in the settlements where they are located because of their student and staff populations. This study developed a questionnaire to measure Hitit University Faculty of Economics and Administrative Sciences students’ motivation to purchase branded products within the context of their spending capacities. The researchers attempted to reach the entire faculty population, and the questionnaires were administered face to face by interviewers. A total of 350 usable questionnaires were obtained. Factor analysis and reliability analysis were applied to the survey data. The factor analysis yielded four factors: factors affecting students’ spending motivation, problems arising from insufficient income, values related to increases in students’ incomes, and students’ perceptions of the price of the brands they use. According to the reported hypothesis tests, no significant difference was found between income level and spending motivation or between gender and spending motivation. The scale demonstrated high reliability (Cronbach’s alpha = .842). Overall, the findings suggest that branded products have a strong effect on students’ spending motivation, that decreases in students’ income do not substantially affect this motivation, and that additional scholarships or monthly earnings may increase it.